Hydraulic approach to Navigli canal daylighting in Milan, Italy. (July 2017) - Sibilla, Stefano; Sciandra, Maria Cristina; Rosso, Renzo; Lamera, Carlotta
Highlights: Hydraulic feasibility of the daylighting of the ancient Navigli canal system in Milan is studied. Hydraulic constraints compared with architectural and urban requirements are evaluated. An optimal solution is found, aimed at restoring the urban landscape of the waterway and its navigability by small cruisers. Secondary use of the waterway for hydropower generation and as source for heat pump systems is also examined. The hydrologic and hydraulic operational rules to restore navigation capability of a man-made, historical canal are provided. Abstract: The daylighting of the ancient Navigli canal system, that encircled Milan medieval downtown over the centuries, is addressed under the municipal commitment towards fully restoring the functional scheme. The program involves both urban planning and architecture to merge the multifaceted issues arising at different scales into a unified design, let alone a number of concerns in both human sciences and technology. Hydraulics is the major driver to address the design process throughout the several spatial scales involved, so the program requires an innovative approach in order to determine water quantity and quality standards under the updated perspective of landscape, recreational and transportation objectives of the program. Hydraulics must ensure maintenance of proper hygienic conditions, visibility of water surface from different viewpoints in the urban landscape and navigability by small cruisers. To this effect, the mathematical model of the canal system reported here demonstrates how one can achieve optimality of flow rate in the re-opened canal by a simulation approach of scenario-driven options, these including the number, location and operating rules of the locks needed to control water levels and transportation fluxes. The model also includes the assessment of inflow availability in both terms of water quantity and quality from the mayor tributary (i.e. Como lake via Adda River) throughout the existing irrigation channel (Naviglio Martesana). The outflow is finally shown to be consistent with the current conveyance of the historical canal (Naviglio Pavese) that conveys the combined outflow of Navigli system, this including the inflow from Lake Maggiore throughout the Naviglio Grande canal and the Adda supply throughout the Naviglio Martesana canal. The results provide the ensemble of hydrologic and hydraulic operational rules to restore navigation capability of the canal system, and to accomplish with land planning, architecture and social requirements of the restoration program, these including hydro-energy exploitation of the restored canal system. The approach demonstrated by the Milan case study can constitute therefore a guideline for daylighting projects of artificial canal systems in historical areas.